Resource mobilization and effective utilization for actualizing community development projects in Nigeria - Abdullahi, Barakatu; Mahmud, Abbas (Kashere Journal of Education, 2023)
This paper examines the resources mobilization and effective utilization for actualizing community development projects in Nigeria. Concepts of resource mobilization for community development project were discusses from different perspectives. Resource mobilization is just a means to the end, the end being the fulfillment of the organization’s vision. Resource mobilization is a team effort, and involves the institution’s commitment to resource mobilization; acceptance for the need to raise resources; and institutionalizing resource mobilization priorities, policies and budget allocation. Problems associated with resource mobilization for community development were discussed. The paper also examines programme implementation for community development projects which identified among others, finding able and willing local leaders, setting up committees and identifying organizations. The paper further discusses participation as one of the basis of community development projects because without participation from the concerns members work or project will not be fully conducted. Various aspect of participation was discussed which include, active participation and functional participation among others. The paper also looks into community development projects evaluation process which centrally discusses empowerment evaluation in which it gives members of community the ability to check and analyze how resources are being utilize for the projects intended for. Conclusion was drawn and way forward were suggested some among others are,